Aspek Hukum dalam Pengelolaan Digital Asset dan NFT: Aspek Hukum dalam Pengelolaan Digital Asset dan NFT - RAUDAH RAUDAH (Program Studi Pascasarjana Magister Hukum Universitas Islam Indragiri, 2024)
This research investigates the legal aspects of digital asset management and Non-Fungible Tokens (NFTs) in Indonesia, aiming to understand the regulatory framework and challenges faced by stakeholders in the digital economy. Utilizing a qualitative approach, the study employs interviews with legal experts, practitioners, and industry stakeholders, combined with a comprehensive review of existing literature and relevant laws. The findings reveal that while there is growing interest in digital assets and NFTs, the legal framework in Indonesia remains fragmented and lacks clarity, leading to uncertainty for users and investors. Key issues identified include the absence of specific regulations governing digital assets, concerns about intellectual property rights, and the need for consumer protection measures. The study concludes that a coherent legal framework is essential to promote innovation and protect stakeholders in the digital asset ecosystem. Recommendations include the establishment of comprehensive regulations that address the unique characteristics of digital assets and NFTs, enhancing legal certainty and fostering a secure environment for digital transactions.